A RETROSPECTIVE ANALYSIS OF FALL FROM HEIGHT CASES AT A TERTIARY CARE HOSPITAL (Journal of Forensic Medicine & Toxicology, 2025)
Objectives: This study was done to prepare and evaluate complete demographic profile of fall from height cases. Methods: This was a retrospective hospital record based study of fall from height cases brought to our hospital U.P.U.M.S., Saifai, Etawah, during the period from September 2022 to August 2023. The age, gender, domiciliary status, manner, site of fall & anatomical region of injuries and outcome where available were reviewed. Results: There were a total of 314 registered cases of fall from height during the study period, of which 297cases had complete data and were included in the study. Most of the cases of fall from height were in the age group 21 to 30 years 98 (33.00%) followed by 31 to 40 years age group 79 (26.60%). Among the total of 297 studied cases, 182(61.27%) were males. Accidental manner 235(79.12%) was the most common. It was determined that 180(60.60%) of the cases had fallen in their homes. Head and face 258(86.86%) and thorax 207(69.69%) were the most affected region. Injury to vertebral system was observed in 174(58.58%) of cases. Full recovery was the outcome in 166(55.89%) of cases. Conclusion: It was found that most of the cases of fall from height were unintentional and can be avoided. For the purpose of developing targeted preventative interventions, variations in the pattern of injuries by age, gender and fall height are crucial.
Keywords: Fall from Height; Anatomical region; Site of fall